2021
DOI: 10.1073/pnas.2024961118
|View full text |Cite
|
Sign up to set email alerts
|

Modeling links softening of myelin and spectrin scaffolds of axons after a concussion to increased vulnerability to repeated injuries

Abstract: Damage to the microtubule lattice, which serves as a rigid cytoskeletal backbone for the axon, is a hallmark mechanical initiator of pathophysiology after concussion. Understanding the mechanical stress transfer from the brain tissue to the axonal cytoskeleton is essential to determine the microtubule lattice’s vulnerability to mechanical injury. Here, we develop an ultrastructural model of the axon’s cytoskeletal architecture to identify the components involved in the dynamic load transfer during injury. Corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 54 publications
1
14
0
Order By: Relevance
“…6,15 Since then, it has been acknowledged that the APMS provides lateral stiffness to the axon via the actin rings 32 and that it shields microtubules from axial stress. 12 It has also been shown that the APMS can act as a tensile shock absorber. 21…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6,15 Since then, it has been acknowledged that the APMS provides lateral stiffness to the axon via the actin rings 32 and that it shields microtubules from axial stress. 12 It has also been shown that the APMS can act as a tensile shock absorber. 21…”
Section: Discussionmentioning
confidence: 99%
“…It was recently shown that the APMS can significantly shield microtubules during applied tissue stress. 12 Additionally, it has been demonstrated that the loss of beta-spectrin, one of the main components of APMS, in C. elegans leads to spontaneous breaking of axons, which is caused by mechanical strains generated by mere animal movement, and that such axon breaking phenotype can be prevented by paralyzing the animal to reduce movement induced mechanical strains. 13,14 It was also recently shown that actin rings are required to maintain microtubule organization.…”
Section: Introductionmentioning
confidence: 99%
“…AFM data based on local indentation of the axonal membrane followed by coarse-grained molecular dynamics simulations also suggest that the spectrin scaffold significantly influences membrane mechanics and that damage to this skeleton can compromise axonal integrity under injury-causing conditions (Zhang et al, 2017). A recent computational analysis of the composite axon further highlights the role of the spectrin scaffold, along with other elements, under concussion or traumatic brain injury-causing conditions (Kant et al, 2021). As long axons are subjected to large deformations during body movements, especially at the joints, or during head impacts, spectrin-based tension buffering mechanisms might have evolved to offer some protection against stretch-induced damage to axons.…”
Section: Mechanical Role Of the Spectrin-based Scaffold In Axonsmentioning
confidence: 97%
“…The mechanical impacts on brain tissue are transient, lasting only milliseconds to microseconds, 3,24 leading to primary mechanical injuries to the axon, including ruptured PM, distorted cytoskeleton and elevated [Ca 2+ ] axon . [25][26][27][28] Most of the current microfluidic-based AoC devices are based on the disruptive axonal severing (axotomy), 5,18,19 or uni-axial overstretching, in which tensile forces are exerted on axons or the substrates to which they tightly adhere longitudinally. 14,20 Although these models significantly advanced our understanding of axonal injury, their flaws persist, including (1) inability to mimic the mechanical stress in transverse directions; (2) incompatibility with live-imaging microscopy to capture the instant subcellular responses during impacts; and (3) inability to restrict the force loading to the axon.…”
Section: Design Of Microfluidic Aoc Device To Mimic Mechanical Force-...mentioning
confidence: 99%